The Influence of Generational Differences on Digital Behavior in Performing Zakat, Infaq, and Sadaqah (ZIS) Using the Theory of Planned Behavior (TPB) Approach - Hilmatunnisa, Alma; Hasanah, Mau’izatil; Rahmah, Nur Khanifatur; Putri, Nuril Mutmainnah; Nurlaeli, Nurlaeli; Muhari, Syafaat (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
The diversity of methods used to distribute zakat is a new challenge that every institution must face. Generational differences in utilizing online zakat platforms reflect technological advancements. For example, Generation Z tends to trust technology more and feels comfortable with cashless transactions, as evidenced by their dominant presence in online zakat contributions. This study aims to identify the factors influencing generational digital behavior in fulfilling Zakat, Infak, and Sedekah (ZIS) obligations and analyze generational differences in zakat behavior through online and offline channels by examining zakat preferences across generations. Consequently, the most effective strategies to encourage active participation in digital philanthropic activities for each generation can be determined. Using a questionnaire involving 200 respondents from various generations who actively use social media, data collection and analysis were carried out using a simple random sampling technique, the statistical method ANCOVA, and the Theory of Planned Behavior (TPB) to identify factors influencing individuals in paying zakat. The findings indicate that generational differences do not have a significant impact. Based on the ANCOVA test, the p-value for the generational variable was 0.302. Meanwhile, the p-value for the education variable was 0.007, with a sum of squares value of 2.018, indicating that education significantly influences the intensity of paying zakat.